2017
DOI: 10.1177/0165025417730681
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of internalizing problems during the transition to adolescence in children with and without conduct problems

Abstract: Children with conduct problems are at greater risk for internalizing problems. The objectives of this study were to (1) examine trajectories of internalizing problems among children with and without clinically significant conduct problems during the transition to adolescence; and (2) identify how academic achievement, peer rejection, parent socioeconomic status, maternal distress, parental warmth, child temperament, and receptive verbal functioning explained differences between the two groups. Children with co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 60 publications
(70 reference statements)
3
13
2
Order By: Relevance
“…Weeks et al (2016) found that the path between externalizing problems to later depressive symptoms was stronger for girls. Contrarily, in Martin-Storey and colleagues (2018), the path from CP to later internalizing problems was significant for boys but not for girls, according to parent ratings. Finally, Yong and colleagues (2014) found that the path from academic difficulties to later internalizing problems was significant for boys but not for girls.…”
Section: The Dual Failure Model and Gendermentioning
confidence: 83%
See 2 more Smart Citations
“…Weeks et al (2016) found that the path between externalizing problems to later depressive symptoms was stronger for girls. Contrarily, in Martin-Storey and colleagues (2018), the path from CP to later internalizing problems was significant for boys but not for girls, according to parent ratings. Finally, Yong and colleagues (2014) found that the path from academic difficulties to later internalizing problems was significant for boys but not for girls.…”
Section: The Dual Failure Model and Gendermentioning
confidence: 83%
“…For girls, neither the social nor the academic failure pathways were found to mediate between CP and depressive symptoms. In Martin-Storey and colleagues (2018), teacher reports showed a significant association between CP and concurrent levels of internalizing problems via lower academic achievement and higher peer rejection, whereas parental reports only showed an indirect association via peer rejection. Using teacher ratings in a community sample, van Lier and colleagues (2012) showed that for boys and girls, externalizing problems at age 6 were linked to internalizing problems at age 8 through poor academic achievement at age 7.…”
Section: Empirical Testing Of the Dual Failure Modelmentioning
confidence: 88%
See 1 more Smart Citation
“…Latent growth curve model (LGCM) was used in the present study to explore the trajectory of externalizing problems. This method allows for the identification of levels of externalizing problems, changes in externalizing problems over time and how marital conflict and RSA activity interact to predict the trajectory of externalizing problems (Martinstorey et al 2018;Singer and Willett 2003).…”
Section: The Present Studymentioning
confidence: 99%
“…Typical features in conduct problems are hatred and causing problems to others (Ogden and Hagen, 2019), engaging in behaviors that violate other's rights such as fighting, intimidating, stealing (Rivenbark et al, 2017) and against social rules such as running away from home and truancy (Wiguna et al, 2016). As a result, adolescents with conduct problems are more vulnerable to problems with family, school and friends (Martin-Storey et al, 2017). Furthermore, they have less motivation to learn, declining academic performance and difficulty to concentrate (Kumara et al, 2017).…”
Section: Introductionmentioning
confidence: 99%